Compliance with multidisciplinary team meeting management recommendations. Issue 6 (10th September 2019) - Samarasinghe, Amali; Chan, Arlene; Hastrich, Diana; Martin, Richard; Gan, Albert; Abdulaziz, Farah; Latham, Margaret; Zissiadis, Yvonne; Taylor, Mandy; Willsher, Peter
Abstract: Objectives: The objective of this study was to evaluate patient compliance with management recommendations given by a breast cancer multidisciplinary team (MDT), assess for reasons for noncompliance, and perform an exploratory assessment on breast cancer outcomes in noncompliant patients. Materials and methods: A retrospective analysis of prospectively collected data was undertaken for patients selected by their primary clinician to be discussed at the MDT of Breast Cancer Research Centre‐WA in Perth between 1st March 2011 and the 28th February 2016. The primary objective was the rate of compliance with MDT management recommendations. Secondary objectives included factors associated with noncompliance, rate of clinical trial uptake, and impact of treatment noncompliance on breast cancer events in a subgroup of early breast cancer (EBC) patients. Results and conclusion: A total of 2614 MDT management recommendations were made for 925 patients. Overall, 92% were compliant with all recommendations given. Clinical trial recruitment was successful in 84.1%. The reasons given for treatment noncompliance were fear of toxicity, choosing an alternative treatment, and treatment inconvenience. In a subset of 337 EBC patients, there was a significantly higher rate of contralateral breast cancer, distant recurrence, and breast cancer‐specific death, P = .0016, in those who were noncompliant. Our study demonstrates a high rate of MDT treatment recommendation compliance and clinical trial recruitment. In a subgroup of EBC patients, noncompliance was associated with significantly worse outcomes. Attention to educating patients to minimize their fear of treatment toxicity and ensuring their understanding of evidence‐based treatment may lead to lower rates of noncompliance.